2007
DOI: 10.1099/vir.0.82879-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of L1, infectious virions and anti-L1 antibody in domestic rabbits infected with cottontail rabbit papillomavirus

Abstract: Shope papillomavirus or cottontail rabbit papillomavirus (CRPV) is one of the first small DNA tumour viruses to be characterized. Although the natural host for CRPV is the cottontail rabbit (Sylvilagus floridanus), CRPV can infect domestic laboratory rabbits (Oryctolagus cuniculus) and induce tumour outgrowth and cancer development. In previous studies, investigators attempted to passage CRPV in domestic rabbits, but achieved very limited success, leading to the suggestion that CRPV infection in domestic rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…2 B). Collectively, these findings prove 165 that CRPV circulating in the blood of rabbits can initiate infection at prewounded cutaneous sites, 166 the preferred sites for CRPV infection, and stimulate anti-viral immune responses in these rabbits 167 just as found in local skin infected animals (Hu et al, 2007a). 168…”
Section: Infections 129mentioning
confidence: 83%
“…2 B). Collectively, these findings prove 165 that CRPV circulating in the blood of rabbits can initiate infection at prewounded cutaneous sites, 166 the preferred sites for CRPV infection, and stimulate anti-viral immune responses in these rabbits 167 just as found in local skin infected animals (Hu et al, 2007a). 168…”
Section: Infections 129mentioning
confidence: 83%
“…Additionally, the CRPV genome can be subjected to a range of PCR-induced mutagenesis events without jeopardizing its functional viability [24]. Finally, our laboratory has shown that domestic rabbits are permissive for CRPV and can be used to study the entire virus life cycle in vivo [29]. These features allowed us to examine the vaccine-induced epitope-specific protective immunity generated against the HLA-A2.1-restricted HPV16E7 82-90 epitope when the epitope is expressed in either a late protein or at the end of an early protein of CRPV.…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, CRPV infection has served as a standard in vivo preclinical model for the development of high-risk-type Human papillomavirus (HPV)-induced malignancy in humans. 3,5,12,25 However, there is difficulty in studying the naturally occurring disease in the laboratory as there are limited commercial supplies available of Sylvilagus spp., and this species does not generally adapt well to captivity. 11 Microscopic examination of affected areas revealed multiple papillary masses lined by stratified squamous epithelial cells with central cores of fibrovascular connective tissue arising from the epidermis as well as parakeratotic hyperkeratosis.…”
Section: <!?Show "Fnote_aff1"$^!"content-markup(/author-grp[1]/aff|/author-grp[1]/dept-list)>mentioning
confidence: 99%